(untitled) (Revista Interação Interdisciplinar (ISSN: 2526-9550), 2023)
Little is known about regional differences in the country regarding performance in Rorschach CS. Objective: to compare the Rorschach normative data for children and adolescents from different Brazilian States. Participants: 371 nonpatient children ages ranging from 5 to 12, 73 nonpatient adolescents ages 13-14. Procedures: The children and adolescents were compared on 57 variables by t-tests and T-scores. For the latter, we investigated whether Brazilian groups presented different performances (T score≥ -5 or +5), having as their parameters the average performances of international samples (ages 5 to 9, 8 to 12, 5 to 18) in T-scores for equivalent age groups (Meyer, personal communication). Results: Through the T-score, we found significant differences in 6 variables between ages 8 to 12 and 7 variables between ages 5 to 9. In adolescents (13 and 14) we found differences in 7 variables. In the article we will discuss the differences obtained while also considering the risk of Type I statistical errors in the exploratory analyses. Conclusion: Children show more variability in general, and it is difficult to say what is cultural; adolescents from São Paulo show themselves as more daring which is in line with living in a very big city. Despite the differences the samples can be grouped to form national samples and additionally show many similarities to international samples.